Divulgence of bacterial diversity and corresponding antibiotic susceptibility profile of coastal waters in Saint Martin's Island, Bangladesh - Nadi, Sauti Malabika; Alam, Marzuq Mohammad; Protiva, Tazrian Jannath (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.